Numerical evaluation of soft inter‐slab joint in concrete‐faced rockfill dam with dual mortar finite element method. (11th January 2018) - Zhou, Mozhen; Zhang, Bingyin; Peng, Chong
Summary: Recently constructed concrete‐faced rockfill dams (CFRDs) often use soft inter‐slab joints to prevent axial compression‐induced extrusion damage in the concrete face. Due to the complexity of the multibody contact and the lack of information on the actual behavior of soft joints, it is highly challenging to numerically assess the effect of soft joints in CFRDs. In this paper, we present a numerical approach for the three‐dimensional modeling of CFRDs with hard and soft joints. A dual mortar finite element method with Lagrange multiplier is developed to treat the multibody contact in hard joints with impenetrability condition. The soft joint slab‐filler‐slab contact system is modeled using an equivalent contact interface approach, where the soft contact constraints are imposed using a perturbed Lagrange formulation. Through a series of laboratory tests, the mechanical behavior of soft joint is investigated. An extrusion model for the soft joint is presented and implemented in the dual mortar finite element method. The proposed numerical method is applied to the three‐dimensional analysis of Tianshengqiao‐1 CFRD. Despite the complex multibody contact and strong material and geometry nonlinearities in the CFRD, the proposed method is stable and capable of capturing salient characteristics of the CFRD. Numerical results show that in Tianshengqiao‐1, the employment of soft joints can effectively reduce the axial compression stress, thus greatly alleviating the risk of extrusion damage in the concrete face.